Analisis Efektifitas Pengelolaan dan Sistem Pengendalian Piutang pada Koperasi Makmur Mandiri di Rengasdengklok - Shabrina Kamilia Fajri; Sihabudin; Meliana Puspitasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Cooperatives, as business entities, are always encouraged to play an active role in providing credit services needed by the community. By providing credit to small and medium businesses, it is hoped that this sector can improve the quality of its activities. This research aims to test and analyze the effectiveness of the Receivables Management and Control System at the Makmur Mandiri Cooperative in Rengasdengklok. The research method used is descriptive with a qualitative approach, with data collection techniques in the form of interviews, observation and documentation. The analytical methods used include analysis of Receivable Turn Over (RTO), Average Collection Period (ACP), Arrears Ratio, Collection Ratio, as well as evaluation of the cooperative control system. The research results show that internal control of receivables at the Makmur Mandiri Cooperative has been implemented in accordance with COSO standards. Although providing credit to cooperatives from 2018 to 2022 is considered quite effective, it still fluctuates every year due to the significant impact of Covid-19 which causes economic uncertainty, resulting in many cooperative members experiencing delays in paying loans at maturity.